Greenhouses in space: from intention to implementation - A. V. Soldatenko; V. F. Pivovarov; O. N. Pyshnaya; L. K. Gurkina; M. M. Tareeva (Овощи России, 2023)
April 12 is Cosmonautics Day, International Day of Human Space Flight. This is a memorable date dedicated to the flight of the first cosmonaut of the planet, Yuri Alekseevich Gagarin, who became a symbol of the earthlings' dream come true. The All-Russian Research Institute of Vegetable Breeding and Seed Production (Federal State Budgetary Scientific Institution Federal Scientific Vegetable Center (FSBSI FSVC)), like a number of other academic institutions, from the beginning of space exploration, got involved in the work to solve the problem of developing food for astronauts and continues research to this day. In the embodiment of the ideas of K.E. Tsiolkovsky and S.P. Korolev on the creation of space greenhouses received a number of significant achievements in the Federal Scientific Vegetable Center, Russian State Agrarian University – Moscow Timiryazev Agricultural Academy, Institute of Biochemical Physics N.M. Emanuel, SSC RF IBMP RAS and others. Varieties of vegetable crops have been created, tested and recommended for weightlessness conditions: radish, Chinese cabbage, dill, lettuce and other rapidly maturing plants. The variety of Chinese Vesnyanka cabbage has successfully passed biotechnical tests on the ground model of the Phytocycle-SD space conveyor greenhouse, during which good production and biochemical parameters were obtained. Russian scientists are conducting research on developing a technology for cultivating various vegetable plants under space flight conditions – in closed ecosystems (synergotrons), which can serve as the basis of life support systems during space flights, at space stations or in space habitats, where some conditions specific for ISS. Studies have been carried out to study tomato plants grown from seeds that have been under space flight conditions for a long time. As a result of the study, a statistically significant increase in the levels of ascorbic acid, polyphenols and carotenoids, the total antioxidant activity of tomato fruits compared to plants grown from control seeds (ground control) was found.